2018
DOI: 10.1016/j.tranon.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The Chemokine Receptor CXCR4 and c-MET Cooperatively Promote Epithelial-Mesenchymal Transition in Gastric Cancer Cells

Abstract: The C-X-C motif chemokine receptor 4 (CXCR4) pathway can promote tumor metastasis but is dependent on cross talk with other signaling pathways. The MET proto-oncogene (c-MET) participates in metastasis and is highly expressed in gastric cancer. However, the relationship between CXCR4 and c-MET signaling and their mechanisms of action in gastric cancer metastasis remain unclear. In this study, in vitro experiments demonstrated that C-X-C motif chemokine ligand 12 (CXCL12)/CXCR4 induces epithelial-mesenchymal tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 39 publications
1
44
0
Order By: Relevance
“…To further elucidate the target mRNAs of miR-204-5p regulation that contributed to the suppressive role of GC metastasis, complementary sequence of miR-204-5p is identified in the 3'-UTR of Chemokine ligand 12 (CXCL12)/chemokine receptor 4 (CXCR4) mRNA by Targetscan. Previous studies have shown the CXCL12/CXCR4 axis is positively associated with the aggressive phenotypes of GC [27][28][29][30]. Further study revealed that CXCL12 and CXCR4 protein expression is increased in GC tissue with lymph nodes (LN) metastatic and mainly expressed in metastatic lymph nodes [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…To further elucidate the target mRNAs of miR-204-5p regulation that contributed to the suppressive role of GC metastasis, complementary sequence of miR-204-5p is identified in the 3'-UTR of Chemokine ligand 12 (CXCL12)/chemokine receptor 4 (CXCR4) mRNA by Targetscan. Previous studies have shown the CXCL12/CXCR4 axis is positively associated with the aggressive phenotypes of GC [27][28][29][30]. Further study revealed that CXCL12 and CXCR4 protein expression is increased in GC tissue with lymph nodes (LN) metastatic and mainly expressed in metastatic lymph nodes [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Radioprotection by CXCL12 might also be relevant in various cancers, in addition to the established role of CXCL12 in supporting epithelial-to-mesenchymal transition that results in cancer metastasis. 17,25,27,28,81,[96][97][98] Using the inducible mouse model to test this will provide a better understanding of the consequence of elevated CXCL12 in a disease state and enable physicians to create better treatment plans.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the elevation of CXCL12 upon stress might be a self-preservation mechanism that cells adopt in emergency conditions. Radioprotection by CXCL12 might also be relevant in various cancers, in addition to the established role of CXCL12 in supporting epithelial-to-mesenchymal transition that results in cancer metastasis (Cheng et al, 2018;Cordeiro Gomes et al, 2016;Domanska et al, 2013;Meng et al, 2018;Ratajczak et al, 2006;Shan et al, 2015;Tang et al, 2019;Teicher and Fricker, 2010;Yu et al, 2017;Zhou et al, 2019). Using the inducible mouse model to test this will provide a better understanding of the consequence of elevated CXCL12 in a disease state and enable physicians to create better treatment plans.…”
Section: Discussionmentioning
confidence: 99%